Translating Latin Medicine in Late-Seventeenth-Century England: Discursive Aspects and Popularizing Strategies - Rovelli, Giulia (Status Quaestionis, 2019)
This paper provides a detailed analysis of the anonymous The Expert Doctors Dispensatory (1657), Bazilica Chymica & Praxis Chymiatricæ (1670) and The Compleat Method of Curing Almost All Diseases (1694), the English translations of three recipe collections which were first published in Latin and, therefore, meant to be circulated among the European medical elite. Following historical pragmatic and historical discourse analytic methodologies, it studies the macro- and microtextual translation methods and procedures, in order to understand to what extent and how the texts accommodated their specialized content to their target audience, namely literate lay readers. The investigation showed that, although the dominant translation method seems to be literal translation, the texts also made extensive use of such accommodating translation procedures as reformulations and partial adaptation, whose purpose is that of creating a version of the source text which might be more acceptable for its target audience, thus granting accessibility and, therefore, playing a fundamental role in the democratization of learned medicine.